Which Skills SME Managers Need to Enter Foreign Markets: An Imperial Study in Vietnamese Agricultural SMEs - Tien Dat, Le (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
In the coming years, Vietnamese agricultural enterprises, many of which are SMEs, are looking forward to numerous development opportunities. In particular, the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) has officially came into effect, opening up great opportunities for the export of agricultural, forestry and fishery products into an extremely large and promising market. However, doing business in the foreign markets, which contain a lot of risks, is not easy for SMEs. Among issues that Vietnamese agricultural export SMEs are facing, poor management capacity is seen as the one of the key constraints. This paper investigates the training needs of Vietnamese agricultural SME managers with regard to skills they need to penetrate international markets. To investigate training needs of Vietnamese SME managers, qualitative methodology with the participation of 124 Vietnamese SME managers was used. A series of market entry skills was emphasized such as those that help to analyze markets, to develop new markets, to get better understanding about potential/ target/ traditional markets. The research results are expected to be useful for SMEs and training/consulting institutions as well as government agencies in developing training programs to support Vietnamese SMEs in exporting agricultural products. The paper also makes a contribution in developing the body of knowledge related to human resource management in emerging markets such as Vietnam.